Pelatihan Pengembangan Media Berbasis Artificial Intelligence untuk Menambah Wawasan Guru MGMP IPA Kabupaten Jember: Training on Media Development Based on Artificial Intelligence to Broaden the Knowledge of Teachers MGMP IPA Northern Region of Jember District - Anggraeni, Firdha Kusuma Ayu; Meilina, Ike Lusi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The integration of artificial intelligence (AI) in the field of science education can facilitate two key objectives: firstly, it can assist teachers in the creation of innovative teaching materials, and secondly, it can enhance the learning experience, making it more engaging and effective. A challenge arises when science teachers, MGMP IPA SMP Northern Region members of Jember, lack the requisite skills to utilize technology effectively. As a solution, teachers are provided with training in the development of AI-based media. The service activities were conducted using the Participatory Action Research (PAR) approach, with the methods employed comprising lectures, discussions, questions and answers, and practical sessions accompanied by the presentation of results. The results of the service activities demonstrated that the participants exhibited a comprehensive understanding of the advantages of AI technology, demonstrated proficiency in utilizing a range of AI-based media, and exhibited the capacity to independently develop AI-based media. Consequently, it can be concluded that through this service activity, it is possible to facilitate changes in teachers' skills, particularly in their ability to utilize technology, with a particular focus on AI-based technologies.